Observation of sore patch in sambar (Rusa unicolour) in Similipal Tiger Reserve, Odisha, India - Palei, Nimain Charan; Rath, Bhakta Padarabinda; Pati, Jagyandatt; Palei, Himanshu Shekhar (Indian Forester, 2019)
No Abstract.